Exposure to long-term ambient air pollution and lung function in adults: a systematic review and meta-analysis - Albina Gross; Rachel Tham; Shyamali C. Dharmage; Martin Röösli; Urs Frey; Olga Gorlanova (European Respiratory Review)
Background The association between long-term ambient air pollution and adult lung function has been inconsistently reported. This systematic review and meta-analysis aimed to quantify the impact of long-term (≥1 year) ambient air pollution on adult lung function. Methods Original articles published between 1 January 2006 and 26 July 2024 were searched in PubMed, Embase and Web of Science. Random-effects models were used to assess the strength of associations of gaseous (nitrogen dioxide and ozone) and particulate matter (PM) pollutants with diameters ≤2.5 and 10 µg, with lung function (forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC ratio). Certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation system (GRADE) approach. Results Of 25 064 potential papers, 27 were included, of which 12 were meta-analysed. There was low-certainty evidence that a 10 µg·m−3 increase in long-term NO2 exposure was associated with lower FEV1 (−15.6 mL, 95% CI −25.0– −6.2; I2=86%; p<0.01) and high-certainty evidence for FVC (−25.3 mL, 95% CI −36.7– −14.0; I2=70%, p<0.01). Similar associations were observed for PM2.5, while long-term exposure to O3 and PM10 were associated with lower FEV1 with high- and moderate-certainty evidence, respectively. Exposure to O3 was associated with lower FEV1/FVC (high-certainty evidence). Interpretation Long-term exposure to ambient air pollution adversely impacts adult lung function. This emphasises the importance of ongoing commitments to mitigating air pollution levels to preserve optimum lung health and prevent premature lung function decline that can lead to earlier and avoidable respiratory diseases.